Characterization of Lethal Zika Virus Infection in AG129 Mice. - Matthew T Aliota; Elizabeth A Caine; Emma C Walker; Katrina E Larkin; Erwin Camacho; Jorge E Osorio (Public Library of Science (PLoS), 2016)
BACKGROUND:Mosquito-borne Zika virus (ZIKV) typically causes a mild and self-limiting illness known as Zika fever, which often is accompanied by maculopapular rash, headache, and myalgia. During the current outbreak in South America, ZIKV infection during pregnancy has been hypothesized to cause microcephaly and other diseases. The detection of ZIKV in fetal brain tissue supports this hypothesis. Because human infections with ZIKV historically have remained sporadic and, until recently, have been limited to small-scale epidemics, neither the disease caused by ZIKV nor the molecular determinants of virulence and/or pathogenicity have been well characterized. Here, we describe a small animal model for wild-type ZIKV of the Asian lineage. METHODOLOGY/PRINCIPAL FINDINGS:Using mice deficient in interferon α/β and Ɣ receptors (AG129 mice), we report that these animals were highly susceptible to ZIKV infection and disease, succumbing within seven to eight days. Rapid viremic dissemination was observed in visceral organs and brain; but only was associated with severe pathologies in the brain and muscle. Finally, these results were consistent across challenge routes, age of mice, and inoculum doses. These data represent a mouse model for ZIKV that is not dependent on adapting ZIKV to intracerebral passage in mice. CONCLUSIONS/SIGNIFICANCE:Foot pad injection of AG129 mice with ZIKV represents a biologically relevant model for studying ZIKV infection and disease development following wild-type virus inoculation without the requirement for adaptation of the virus or intracerebral delivery of the virus. This newly developed Zika disease model can be exploited to identify determinants of ZIKV virulence and reveal molecular mechanisms that control the virus-host interaction, providing a framework for rational design of acute phase therapeutics and for vaccine efficacy testing.